Needs Analysis for the Development of Microlearning-Based Chinese Reading Instruction: Analisis Kebutuhan Pembelajaran Membaca Bahasa Mandarin Berbasis Microlearning - Siti Handayani; Ifan Iskandar; Yumna Rasyid (Academia Open, 2027)
General Background: Reading is a fundamental competency in Chinese language learning, requiring mastery of phonetics, Hanyu Pinyin, Chinese characters, vocabulary, and text comprehension. Specific Background: University students continue to experience difficulties with Mandarin pronunciation, character recognition, and basic text comprehension, while existing instructional resources require additional audio, video, and interactive support. Knowledge Gap: Although printed and digital Chinese learning materials are available, resources integrating reading content, phonetic instruction, audiovisual media, and learning activities within an accessible format remain necessary. Aims: This descriptive quantitative study, supported by qualitative data, analyzed basic Chinese reading learning needs as a foundation for developing microlearning-based digital materials using questionnaires from 56 students and an instructor interview. Results: Major pronunciation difficulties involved initial zh (46.43%), ch (37.50%), and q (21.43%); final ü (69.64%); third tone (57.14%); and second tone (44.64%). Character recognition was difficult for 57.14% of students. Moreover, 85.71% required simple-text exercises with interactive explanations, while 71.42% required phonetic exercises. Digital learning innovation received a mean score of 4.16. Novelty: The needs analysis combines learner and instructor perspectives to specify content, media, and independent-practice requirements for microlearning-based materials. Implications: Digital materials should integrate pronunciation instruction, character recognition, vocabulary and word-class information, simple texts, audio, video, and interactive exercises in short, focused, accessible learning units. Highlights: Final ü recorded the highest pronunciation difficulty at 69.64%. Chinese character recognition was reported as difficult by 57.14% of students. Interactive simple-text practice was requested by 85.71%, while 71.42% requested pronunciation exercises. Keywords: Needs Analysis, Digital Teaching Materials, Chinese Reading, Microlearning